The zoon r package for reproducible and shareable species distribution modelling. Issue 2 (18th September 2017) - Golding, Nick; August, Tom A.; Lucas, Tim C. D.; Gavaghan, David J.; van Loon, E. Emiel; McInerny, Greg
Abstract: The rapid growth of species distribution modelling (SDM) as an ecological discipline has resulted in a large and diverse set of methods and software for constructing and evaluating SDMs. The disjointed nature of the current SDM research environment hinders evaluation of new methods, synthesis of current knowledge and the dissemination of new methods to SDM users. The zoon r package aims to overcome these problems by providing a modular framework for constructing reproducible SDM workflows. zoon modules are interoperable snippets of r code, each carrying a SDM method that zoon combines into a single analysis object. Rather than defining these modules, zoon draws modules from an open, version‐controlled online repository. zoon makes it easy for SDM researchers to contribute modules to this repository, enabling others to rapidly deploy new methods in their own workflows or to compare alternative methods. Each workflow object created by zoon is a rerunnable record of the data, code and results of an entire SDM analysis. This can then be easily shared, scrutinised, reproduced and extended by the whole SDM research community. We explain how zoon works and demonstrate how it can be used to construct a completely reproducible SDM analyses, create and share a new module, and perform a methodological comparison study.